Methamphetamine promotes a-tubulin deacetylation in endothelial cells: The protective role of acetyl-L-carnitine - Fernandes, Sílvia (2015)
Methamphetamine (METH) is a powerful psychostimulant drug used worldwide for its reinforcing properties. In addition to the classic long-lasting monoaminergic-disrupting effects extensively described in the literature, METH has been consistently reported to increase blood brain barrier (BBB) permeability, both in vivo and in vitro, as a result of tight junction and cytoskeleton disarrangement. Microtubules play a critical role in cell stability, which relies on post-translational modifications such as a-tubulin acetylation. As there is evidence that psychostimulants drugs modulate the expression of histone deacetylases (HDACs), we hypothesized that in endothelial cells METH-mediation of cytoplasmatic HDAC6 activity could affect tubulin acetylation and further contribute to BBB dysfunction. To validate our hypothesis, we exposed the bEnd.3 endothelial cells to increasing doses of METH and verified that itleads to an extensivea-tubulin deacetylation mediated by HDACs activation. Furthermore, since we recently reported that acetyl-L-carnitine (ALC), a natural occurring compound, prevents BBB structural loss in a context of METH exposure, we reasoned that ALC could also preserve the acetylation of microtubules under METH action. The present results confirm that ALC is able to prevent METH-induced deacetylation providing effective protection on microtubule acetylation. Although further investigation is still needed, HDACs regulation may become a new therapeutic target for ALC.